The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s1413-70542012000200006
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and pollen viability of Lolium multiflorum Lam.

Abstract: Study and characterization of pollen grains are essential for different areas, especially taxonomy, genetic improvement, phylogeny, and paleobotany. As yet, there are no reports on pollen morphology of genotypes of naturalized Lolium multiflorum Lam., introduced cultivars or breeding populations, diploid or polyploid. Ten genotypes of annual ryegrass (L. multiflorum) were evaluated for the viability of pollen grains using propionic carmine and Alexander's stains, while morphology was assessed by the acetolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…13 The same occurred with Avena strigosa and Avena sativa with pollen grains previously measured 42 and 16 with pollen size similar to our study. In the pollen grains of Lolium multiflorum, we observed sizes slightly larger than those measured, 12 on the other hand, our measurements are similar to those obtained by 11 who also described the pollen grains of this specie. While Poa annua showed pollen grains of similar size to the same species described by Salgado-Labouriau and, 18 the size of the pollen grain of Triticum sp.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…13 The same occurred with Avena strigosa and Avena sativa with pollen grains previously measured 42 and 16 with pollen size similar to our study. In the pollen grains of Lolium multiflorum, we observed sizes slightly larger than those measured, 12 on the other hand, our measurements are similar to those obtained by 11 who also described the pollen grains of this specie. While Poa annua showed pollen grains of similar size to the same species described by Salgado-Labouriau and, 18 the size of the pollen grain of Triticum sp.…”
Section: Discussionsupporting
confidence: 91%
“…10 On the other hand, other cultivated species such as ryegrass (Lolium multiflorum) have pollen grains that cannot be distinguished from native Brazilian taxa. 11,12 Figure 1 Pollen grains records of Zea mays (corn) in Quaternary sediments of Rio Grande do Sul state and the ages what the pollen of Zea mays were founded in the sediment according to. [4][5][6][7] The other studies on pollen grains of cultivated grasses focused on the analysis of the exine surfaces by scanning electron microscopy of species of rice-Oryza, 13,14 sugar cane-Saccharum, 15 oat-Avena [14][15][16][17] and wheat-Triticum.…”
Section: Introductionmentioning
confidence: 99%
“…On all treatments except the control, seeds of winter‐growing species were introduced by oversowing. Italian ryegrass ( L. multiflorum genotype Comum) (Nunes et al ., ; MAPA, ) and arrowleaf clover ( T. vesiculosum cv. Yuchi) (Frame, ) were oversown in lines on to the surface of the natural grassland sward at seeding rates of 30 and 12 kg ha −1 , respectively, on 29 May 1997.…”
Section: Methodsmentioning
confidence: 99%
“…Studies by Nunes et al (2012) with genotypes of Lolium multiflorum, including two tetraploids, showed higher rates (above 90%) of pollen viability. The authors suggested that the high rate of functional pollen in these genotypes may be associated with meiotic regularity and regular collection timings (8:30 a.m. to 10:00 a.m.) when anther dehiscence begins, implying that viability reaches its maximum.…”
Section: Resultsmentioning
confidence: 92%